KETIKA KOMPENSASI MANAJEMEN BERPERAN DALAM MENINGKATKAN NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI PEMEDIASI - Rendy Mirwan Aspirandi (Jurnal Ilmiah Akuntansi Indonesia, 2017)
Abstract: This study examines the effect of management compensation on firm value. In addition, this study also examines the role of mediation of financial performance on the effect of management compensation on firm value. Analytical technique using PLS (Partial Least Square). The research population is a manufacturing sector company listed on the Indonesia Stock Exchange in 2010-2014. The results show some findings. First, an increase in management compensation will also increase the firm value. Second, financial performance acts as a mediator of the influence of management compensation on firm value. The type of mediation of financial performance is partial mediation.Keywords: Management Compensation, Financial Performance, and Firm Value